Yuridis Pemberian Kredit Bank dengan Jaminan Hak Tanggungan pada PT. Bank Mestika Dharma, Medan - Evelin Wijaya; Fendy Fendy; Aisyah Aisyah (Mahesa Research Center, 2020)
The purpose of this study is to examine the policies of granting credit in PT. Bank Mestika Dharma, TBK along with bonded legality of credit agreement with mortgage guarantee and to find out legal certainty for creditors who hold mortgage rights guarantee. The method of this research is descriptive analytic where the facts found are described in general along with their legal provisions. This research is carried out by doing on the spot and books research by looking the problems and compared with laws and/or implementing regulations which related to the binding of these mortgage rights guarantee. The results of this research is knowing that the collateral binding is very important for all financial institutions which perform their function as intermediation. In PT. bank Mestika Dharma, TBK, every credit must have credit agreement by binding certain guarantees, one of them is mortgage rights guarantee as regulated in UU No.4 in 1996 where this right will give creditor who have this mortgage rights guarantee to take precedence in obtaining payment of the claim from the sale of objects belonging to the debtor and based on the binding value rather than othe creditors in paying their obligation.